2012
DOI: 10.1002/hep.25736
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E1 controls proliferation of hepatic stellate cells and is essential for liver fibrogenesis in mice

Abstract: Liver fibrogenesis is associated with the transition of quiescent hepatocytes and hepatic stellate cells (HSC) into the cell cycle. Exit from quiescence is controlled by E-type cyclins (CcnE1, CcnE2). Thus, the aim of the current study was to investigate the contribution of E-type cyclins for liver fibrosis in man and mice. Expression of CcnE1, but not of its homologue CcnE2 was induced in fibrotic and cirrhotic livers from human patients with different etiologies and in murine wildtype (WT) livers after perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 24 publications
7
56
0
Order By: Relevance
“…21 It has been reported that cyclin E1 can interact with CDK2 and activate CDK2 at the G 1 /S transition of the cell cycle. 22,23 In the present study, protein gel blotting analysis indicated that the expression levels of cyclin E1 and CDK2 proteins were upregulated after 12 h of incubation with vitamin C, which suggests that cyclin E1 and CDK2 may involved in the transition of cell cycle from G 1 to S phase in the ADSCs. The p53 protein is an important regulative factor of many processes necessary for the proper cellular function, and is also responsible for the regulation of cell cycle.…”
Section: Discussionsupporting
confidence: 53%
“…21 It has been reported that cyclin E1 can interact with CDK2 and activate CDK2 at the G 1 /S transition of the cell cycle. 22,23 In the present study, protein gel blotting analysis indicated that the expression levels of cyclin E1 and CDK2 proteins were upregulated after 12 h of incubation with vitamin C, which suggests that cyclin E1 and CDK2 may involved in the transition of cell cycle from G 1 to S phase in the ADSCs. The p53 protein is an important regulative factor of many processes necessary for the proper cellular function, and is also responsible for the regulation of cell cycle.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, in this model, c-myc was not required for cyclin E1 mediated HSC activation. Several other levels of control may exist for cyclin E1, as it appears to be negatively regulated by cyclin E2 [141] and miR-195 [142]. In a human immortalized HSC line (LX-2) in culture, spontaneous activation is associated with a reduction in miR-195, an increase in cyclin E1, and entry into the cell cycle with subsequent proliferation [142].…”
Section: New and Emerging Pathways Of Hsc Activationmentioning
confidence: 98%
“…However, in view of how HSCs and a fibrotic microenvironment promote HCC [14], some of the observed results in the in vivo model may have been due to reduced c-myc expression and attenuated HSC activation, but again, these parameters were not directly measured. Cyclin E1 is known to be under the control of c-myc and is critical for HSC activation [141]. As with c-myc, cyclin E1 is highly expressed in cirrhotic human liver tissue and not only promotes the transdifferentiation of quiescent HSCs but drives the proliferation of activated myofibroblasts.…”
Section: New and Emerging Pathways Of Hsc Activationmentioning
confidence: 99%
“…HSC were isolated from adult male mice in a C57BL/6 background weighting approximately 25 g following the collagenase method as described recently [17]. Freshly isolated HSC were washed and plated in 6-well plates (Falcon) at a density of 150,000 cells per well and cultivated in DMEM supplemented with 10% FCS 4 mmol/l Lglutamine and 4 mmol/l penicillin/streptomycin (PAA, Pasching, Austria).…”
Section: Isolation Of Hepatic Stellate Cells (Hsc) and Primary Hepatomentioning
confidence: 99%
“…Thus, regeneration of hepatocytes and activation of HSCs during chronic liver injury involves transition of these normally quiescent cells into the cell cycle leading to cell proliferation. We recently demonstrated that the cell cycle mediator cyclin E1 is essential for proliferation and activation of HSC but less relevant for proliferation of regenerating hepatocytes [17,18]. However, the role of c-myc -which is thought to act upstream of cyclin E1 -for initiation and progression of liver fibrosis is largely unknown.…”
Section: Introductionmentioning
confidence: 98%